ANALYSIS OF PHYTOPLANKTON DISTRIBUTION AT THE SOUTH-WESTERN COAST OF ISTANBUL UTILIZING GIS - Say, Ayse Neslihan Ozman; Sivri, Nuket; Erturk, Ali; Seker, Dursun Zafer; Li Fusheng (Parlar Scientific Publications (P S P), 2010)
Marmara Sea, located between the European and Asian continents, is an important aquatic ecosystem for Turkey Together with the Bosphorus and the Dardanelles, it forms the Turkish Strait System that is an internationally important waterway From the ecological viewpoint, Marmara Sea is under high stress because of the municipal, industrial and agricultural sources of pollution as well as the intensive maritime activities, and is at risk of extensive environmental deterioration because of eutrophication The mostly populated districts of Istanbul are located at the coastal areas of the Marmara Sea In this study, chlorophyll-a and phytoplankton were monitored at the southwestern coast of Istanbul Phytoplankton species were analyzed quantitatively In general, Bacillariophyceae were found to be dominant in all the monitoring stations Cyano phyceae and Dinophyceae abundance has increased in spring Seasonal variation in phytoplankton succession was found to be related to temperature In this study, besides from bloom-forming Gymnodinium spp as Dinoflagellate members, other Dinoflagellates (Prorocentrum micans and Ceratium furca) were observed as harmful algal bloom-forming species All the results obtained by data analysis were visualized using Geographical Information System (GIS) as an initial effort to develop a local phytoplanktonic species atlas which will be important for environmental management
Keywords: Harmful algal bloom; Istanbul coast; Marmara Sea; phytoplankton distribution